Thermo-Fluid Effects Associated with Modelling Subscale Automotive Heat Exchangers - Gerova, Klementina (Cranfield University, 2015)
Automotive components are tested extensively in wind tunnels by automotive manufacturers and race teams. This is usually achieved using an accurate scale model representation of the component within the wind tunnel. Automotive heat exchangers, however, are comprised of numerous intricate geometries and are therefore impractical to produce at model scale. Instead they are simply modelled as pressure drops, achieved using a thin mesh or honeycomb of known porosity. Most commercial computational fluid dynamics solvers ignore the geometry of the heat exchanger and instead model it as a discontinuity with a known pressure drop and heat transfer. The pressure drop across an automotive heat exchanger, however, was found to vary with both the coolant temperature and the angle of inclination of the heat exchanger. This thesis initially presents a relationship between the pressure drop coefficient and the inclination angle for varying media porosities. Mathematical relationships for inclination angles of 0°, 15°, 30° and 45°. were derived relating this pressure drop coefficient to the porosity of the media. Weighted least squares is proposed over ordinary least squares when obtaining the Forchheimer equation coefficients from experimental measurements. Investigation extends into the thermo-fluid effects on a full scale automotive heat exchanger when inclined at 0 °, 15°, 30° and 45°. It was found, depending on the angle, that there was a difference in the pressure drop of up to 10% between the unheated and heated (100 C) heat exchanger. Based on the proposed mathematical relationship, this correlated to a 4% decrease in porosity in order to accurately model the automotive heat exchanger at subscale. The thesis concludes with experimental and numerical investigation into the heat transfer on a hydrodynamically and thermally developing ow within a radiator channel. Laser doppler anemometry measurements recorded a 1.5% increase in the centreline velocity compared to 0.8% obtained from numerical simulation.
Keywords: Automotive heat transfer; Wind tunnel radiator modelling; Subscale radiators; Developing radiator matrix channel flow; Thermally developing flow